Agronomic Performance, Variance Components, and Clustering in Vernonia galamensis Germplasm from Ethiopia - Alemneh Mideksa; Kassahun Tesfaye (International Journal of Agronomy)
This study was conducted to assess the agronomic performance, variance components, and clustering analysis of 80 accessions of Vernonia galamensis, in alpha-lattice design with two replications at Melka Werer and Wondo Genet agricultural research centers in 2018/19. The one-way ANOVA showed that the high significant variation (p<0.05) for most of the quantitative traits among accessions except for days to emergence, and the mean performance of seed yield per hectare ranged from 348.9 to 624.3 kg ha−1, with an average of 474.4 kg ha−1. The result of principal component analysis indicated that those exhibited more than one eigenvalue were about 71.0% of variability. While the cluster analysis based on 80% of similarity into eight clusters from the eighty accessions, the first cluster had the largest number of accessions. Overall, the study confirmed that the agromorphological characters such as the number of heads per plant, number of seeds per head, seed yield per plant, and seed weight per plot were the main contributors for seed yield per hectare in V. galamensis.